Keterampilan bahasa Arab sebagai kompetensi komunikatif dalam pendidikan - Zahrah, Humaira; Salsabila, Feliska; Farlyan, Muhammad; Gumay, Rantika; Daviza, Tasya Putri (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
Speaking skills are a crucial element in effective communication in academic and professional settings. In addition to grammatical accuracy, good communication requires the ability to use language appropriately in social contexts, construct coherent speech, and apply appropriate communication strategies. This study examines three indicators of communicative competence according to Dell Hymes (1972) in supporting academic and professional interactions. The method used was a literature review of research conducted during the 2014–2024 period. The results of the study indicate that Arabic language learning still faces major obstacles in contextual language use, speech coherence, and communication strategies. Learning tends to emphasize linguistic aspects, while aspects of appropriateness and performance are less considered. As a result, students excel grammatically but are less effective in communicating across social contexts.